The role of (Christian) spirituality in the economy in the light of Laudato si' - Platovnjak, Ivan (Array, 2019)
The global economic crises at the beginning of the third millennium revealed the harmful consequences for the whole of society and the environment that the myth of the “deified” economy brings. Many researchers have been encouraged to begin exploring the causes of crises intensively. The author thinks that it is more important to look for ways to implement the economy in a way that serves the common good and a common home. The path to renewal of the economy the author sees described primarily in the direction that Pope Francis presented in the Laudato si'. Therefore, he puts forward the thesis that in the light of Laudato si' (Christian) spirituality plays an important role in the economy. To confirm the thesis, the author briefly defines economics and spirituality. Then follows a presentation of fundamental orientations based on the analysis in Laudato si' that could enable economic recovery. In the end, the author describes how a renewed Christian spirituality and dialogue can help individuals and communities make basic guidelines for a new economy.